Studying mathematics around Keraton Yogyakarta - Luluk Mauluah (Universitas negeri Yogyakarta, 2022)
Studying mathematics in elementary school using cultural resources can make the learning process more meaningful. Students can explore learning resources for mathematics at the Yogyakarta Palace while getting to know the local culture. Learning resources that can be used for elementary school mathematics learning include gunungan sekaten, batik, the Bangsal Manganti hall, the stairs at the palace, etc. Based on the analysis carried out by the researcher, the identified learning resources at the Kraton can be used for Grades 1 to 6. From D’Ambrosio's theory of classification of ethnomathematics activities, there are 5 categories of learning resources in the Palace, including counting, weighing, measuring, ordering and classifying which can be used in elementary school mathematics learning.